ANALYSIS OF STRUCTURE RELIABILITY OF UTSMAN BIN AFFAN BUILDING (Case Study : Sekolah Islam Terpadu Aliya Bogor) - Lutfi, Muhamad; Maulana, Ayub (ASTONJADRO, 2020)
Indonesia's tectonic conditions at the meeting of the world's large plates and several small plates that cause the area associated with earthquakes, based on data from the Bogor City Disaster Mitigation, Bogor City is located in an earthquake prone area. Sekolah Islam Terpadu Aliya Bogor is located at Jalan Gardu Raya No. 03, Bubulak, Kecamatan Bogor Barat, Kota Bogor. This study evolved the structure of the school building in terms of the structure of the column and beam elements for the safety and security of its inhabitants. The buildings analyzed were Utsman Bin Affan building TK A and TK B which functioned as places for learning and teaching. The research method starts by analyzing the existing conditions, checking the quality of the concrete, then analyzing the structure using the help of the ETABS V9.7.4 program, and analyzing the column structure using the spColumn program. Structural modeling published in SNI 1727-2013 (concerning loading), SNI 2847-2013 (concerning concrete structure requirements), SNI 1726-2012 (regarding earthquake repair planning), and PPIUG-1983 (concerning Indonesian loading regulations for buildings). The results of the analysis of the Utsman Bin Affan building with 2-story building specifications column dimensions 25 x 25 cm, beams 20 x 40 cm, column concrete quality fc '= 24.74 MPa, concrete beam quality fc' = 26, 59 MPa, principal reinforcement D16 with fy = 390 MPa, shear reinforcement í˜10 Fy = 240 MPa, the results of analysis of existing columns and beams are in accordance with the requirements of SNI 2847-2013, based on that the buildings are approved, and the result of analysis beams does not exceed strength (O / S).